Development of environmental safety and health conceptual model for steel factory / Nur Shuhada Bt. Mohamed Jaafar - Nur Shuhada, Mohamed Jaafar (2013)

(untitled)
Since modernization and industrialization have led to human loss and tragedies, due to industrial accidents all over the world, it is significant to look at the aspects that lead to success of environmental safety and health (ESH) situation. The safety statistics indicate high fatality and injury rates among the manufacturing employees. This paper focuses on developing an ESH Conceptual Model, based on related recommended OSHMS models in the existing of OHSAS: 18001 Standard and Guidelines. Besides, the effectiveness of OSHMS implementation was evaluated, by identifying the potential hazards and practical methods in minimizing workplace accidents. A case study has been conducted at Steel Factory Sdn. Bhd. which is located in Selangor that has implemented OSHMS, with the certification on OHSAS: 18000 in Year 2008. The methodologies consisted of review of the company’s data, documentations and literature review, questionnaire surveys, site surveys, site observations, safety inspection checklist and site interviews. The findings from this study indicated that, based on Company’ Yearly Incident Case Comparism (Year 2005 until Year 2011), by the implementation of OSHMS in Year 2008, it shows the reduction of fatal and major cases, from 27 cases in Year 2009 and 25 cases in Year 2010, decreased to 16 cases of reported to ESH Department in Year 2011. The employees’ attitude and behaviour were the main factors that contribute to accidents. The potential hazards and practical methods have been identified by Hazard Identification, Risk Assessment and Risk Control (HIRARC) method, based on Guideline of HIRARC by DOSH, 2008. As a result, the health hazard, safety hazard and environmental hazard were the potential hazards identified in this study. A sophisticated approach was implemented by the management to control and prevent the hazards, which includes the elimination of the source, engineering controls, administration controls and implementation of the PPE. Many programs and training were provided by management to increase safety iii awareness and decrease the accident occurrences among employees. Other than that, there are three important elements which lead to the successful of OSHMS identified in developing the ESH Conceptual Model for the steel factory, which includes the management leadership and organizational commitment, potential hazard identification and also practical methods and prevention. By understanding the OSHMS concept, the application of legislation that needs to be followed by industries is easily to be understood, where evidences showed that various benefits could be yielded from OSHMS implementation which includes the reduction of death and injury rates at the steel factory.